2017
DOI: 10.15171/ijbsm.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vitamin and Mineral Intakes in Paralympic Athletes in Tabriz, Iran

Abstract: Introduction: Paralympic games are the most important competitions for disabled people in the world. Nowadays the role of nutrition is undeniable in physical exercises and the deficiency of micronutrients leads to poor performance by athletes, so our aim was to assess vitamin and mineral intakes in elite Paralympic athletes in Tabriz. Methods: Thirty-five elite Paralympic athletes (24 men and 11 women) took part in this study. Three-day self-reported food diaries were analyzed for vitamins and nutrients and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This may be partly because of their greater intake of foods such as fruit that contain water [ 53 ]. Several studies have found that athletes do not meet the recommendations for total water, potassium, iron, magnesium, calcium, manganese, chromium, zinc, molybdenum, and selenium and consume too much sodium [ 9 , 16 , 20 , 21 , 24 , 27 , 61 , 65 , 66 , 67 , 68 ]. Water and electrolytes are needed for fluid balance and poor hydration can negatively affect training sessions and performance and lead to heat exhaustion, particularly in the southern regions of the U.S. where the majority of our study sample resided [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be partly because of their greater intake of foods such as fruit that contain water [ 53 ]. Several studies have found that athletes do not meet the recommendations for total water, potassium, iron, magnesium, calcium, manganese, chromium, zinc, molybdenum, and selenium and consume too much sodium [ 9 , 16 , 20 , 21 , 24 , 27 , 61 , 65 , 66 , 67 , 68 ]. Water and electrolytes are needed for fluid balance and poor hydration can negatively affect training sessions and performance and lead to heat exhaustion, particularly in the southern regions of the U.S. where the majority of our study sample resided [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings multiple studies have found that many athletes consume more total fat than the recommended amount (20–35% energy) [ 15 , 16 , 19 ]. Besides inadequate consumption of several macronutrients, many athletes have reported inadequate intakes of thiamin, riboflavin, niacin, vitamin B 6 , vitamin B 12 , pantothenic acid, biotin, folate, vitamins A, C, D, E, and K, potassium, calcium, zinc, phosphorus, manganese, chromium, molybdenum, selenium, and magnesium [ 9 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Further, female athletes are less likely to meet the recommendations for iron intake compared to male athletes [ 9 , 16 , 18 , 20 , 27 ] and female athletes may have lower intakes of vitamin B 12 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%